EVALUATING THE MPUMALANGA ARTS AND CULTURE COUNCIL ACT - Shabangu, Millicent Nomsa (My University, 2011)
In accordance with the principles of redress and affirmative action, the postapartheid South African government has identified the need for transformation of the arts and culture dispensation. The ongoing exploitation of artists and cultural groups has been a concern. The national Department of Arts and Culture developed the National Arts Council (NAC) Act intended for the creation, promotion and protection of South African arts and culture. This study examined the implementation process of the NAC Act in Mpumalanga and concludes with recommendations. The study relied on qualitative research, collected through interviews. Some of the findings of the research were that institutional arrangements were not made; and that there is no system for monitoring and evaluation within the Department of Sport, Recreation, Arts and Culture. It is recommended that institutional arrangements should be made on the reporting system within the department; that suitable mechanisms be put in place to monitor the department’s expenditure; and that a monitoring and evaluation system should be developed.
MM - P&DM
Keywords: Performance evaluation; Mpumalanga Arts and Culture Council Act